Simulated-based engineering of complex - Clymer, John R. (J. Wiley, 2009)
Beginning with an introduction to SBSE, the book covers: Simulation concepts and building blocks; Systems design and model development; Markov model development; Reliability processes; Queuing theory in SBSE; Rule-based learning and adaptation; Agent motion and spatial interactions; Multi-agent system of systems.